2006
DOI: 10.2174/156720206778792894
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Circuitry and Peripheral Neural Sympathetic Activity Responsible for Essential Hypertension

Abstract: Both clinical and experimental studies dealing with patients affected by idiopathic or essential hypertension (EH) are devoted to the great deal of physiological, pharmacological and pathological as well as therapeutical issues of EH. However, most articles devoted to EH do not refer to the central nervous system mechanisms underlying this disease and the channels which allow that these mechanisms are funneled to the peripheral autonomic nervous system and trigger this cardiovascular disorder. In the present r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 178 publications
(265 reference statements)
0
22
0
Order By: Relevance
“…Furthermore, considering that both CNS nuclei interchange inhibitory axons, alpha-2 agonists and/or antagonists are able to revert the physiological predominance of any of both systems. In addition, it is important to know that whereas the C1-Ad nuclei are positively correlated with the dorsal raphe (DR) serotonergic nucleus, the A5-NA nucleus parallels the activity of the median raphe (MR) serotonergic nucleus (MR-5HT) [103,104]. Finally, it should be known that both serotonergic nuclei interchange inhibitory axons.…”
Section: Malignant Diseases Xmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, considering that both CNS nuclei interchange inhibitory axons, alpha-2 agonists and/or antagonists are able to revert the physiological predominance of any of both systems. In addition, it is important to know that whereas the C1-Ad nuclei are positively correlated with the dorsal raphe (DR) serotonergic nucleus, the A5-NA nucleus parallels the activity of the median raphe (MR) serotonergic nucleus (MR-5HT) [103,104]. Finally, it should be known that both serotonergic nuclei interchange inhibitory axons.…”
Section: Malignant Diseases Xmentioning
confidence: 99%
“…Finally, it should be known that both serotonergic nuclei interchange inhibitory axons. Summarizing the above, it has been established that whereas the DR-5HT + C1-Ad hyperactivity is responsible for the uncoping stress syndrome, the MR-5HT + A5-NA binomial predominates in patients affected by endogenous depression as well as in patients affected by neural sympathetic overactivity (essential hypertension, hyperinsulinism, rheumatoid arthritis, and all TH-1 autoimmune diseases) [3,24,[101][102][103][104][105]. At the gastrointestinal level, patients with reflux esophagitis [81,82] Figs.…”
Section: Malignant Diseases Xmentioning
confidence: 99%
“…Finally, the above tests have been carried out during both relapsing and remission periods. The information derived from that research work has allowed us to understand the pathophysiological mechanisms which underlie most type of diseases: gastrointestinal, cardiovascular, endocrinological, neurological, psychiatric and others; and in addition, to be the first to demonstrate the neuroautonomic profiles which *Address correspondence to this author at the Departments of Neurophysiology, Neurochemistry, Neuropharmacology and Neuroimmunology, Instituto de Medicina Experimental, Faculty of Medicine, Universidad Central de Venezuela, Caracas, Venezuela; E-mail: flechin@movistar.net.ve underlie psychosis [20][21][22][23], endogenous depression [4,24], hyperinsulinism [8, [24][25][26][27][28][29][30][31], biliary dyskinesia [32][33][34], ulcerative colitis [35], infertility [26,36], duodenal ulcer and gastritis [37,38], irritable bowel syndrome [39][40][41][42][43], Crohn's diseases [44,45], pancreatitis [45][46][47][48], essential hypertension [6, 49,50], thrombocytopenic purpura [51], polycythemia vera [52], myasthenia gravis [53], reactive hypoglycemia [8], cardiovascular and pulmonary disorders [53]<...>…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the above, it should be known that the C1(Ad) nuclei interchanges inhibitory axons with A5(NA) pontomedullary nucleus, responsible for neural sympathetic activity [45,46] thus, the disappearance of the activity of the former, triggered by tianeptine minimized the peripheral adrenal sympathetic drive and favored the absolute predominance of the neural sympathetic activity registered in the present study. With respect to the latter, exhaustive evidence has demonstrated that insulin crosses the blood brain barrier and excites the A5(NA) nucleus responsible for the activity of sympathetic nerves [9,[47][48][49]. It is well known that at CNS level, tianeptine triggers the absolute disappearance of 5-HT from synaptic clefts.…”
Section: Peripheral Mechanismsmentioning
confidence: 99%